2012
DOI: 10.1074/jbc.m112.393603
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of the Ethanol-induced Potentiation of α1 Glycine Receptor by a Small Peptide That Interferes with Gβγ Binding

Abstract: Background: G␤␥ interaction with GlyR is an important determinant in ethanol potentiation of this channel. Results: A small peptide, RQH C7, can inhibit ethanol potentiation of GlyR currents. Conclusion: Results with RQH C7 indicate that ethanol mediated potentiation of GlyR is in part by G␤␥ activation. Significance: Molecular interaction between G␤␥ and GlyR could be used as a target for pharmacological modification of ethanol effects.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
21
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 16 publications
(22 citation statements)
references
References 49 publications
0
21
0
Order By: Relevance
“…For example, basic residues in the intracellular loop domain have been shown to mediate ethanol effects via binding to Gbg proteins (Yevenes et al, 2010). A peptide designed to mimic the critical loop region disrupted ethanol potentiation without affecting other Gbg signaling pathways (San Martin et al, 2012) and has been proposed as an intoxication therapeutic. Binding of zinc to residues in the extracellular domain has also been shown to sensitize glycine receptors to both agonist and ethanol, possibly in a synergistic manner (McCracken et al, 2010).…”
Section: A Eukaryotic Inhibitory Channelsmentioning
confidence: 99%
“…For example, basic residues in the intracellular loop domain have been shown to mediate ethanol effects via binding to Gbg proteins (Yevenes et al, 2010). A peptide designed to mimic the critical loop region disrupted ethanol potentiation without affecting other Gbg signaling pathways (San Martin et al, 2012) and has been proposed as an intoxication therapeutic. Binding of zinc to residues in the extracellular domain has also been shown to sensitize glycine receptors to both agonist and ethanol, possibly in a synergistic manner (McCracken et al, 2010).…”
Section: A Eukaryotic Inhibitory Channelsmentioning
confidence: 99%
“…However, it is also well documented that determinants of the ethanol sensitivity of a1 subunit GlyRs can be located intracellularly, such as protein kinase C phosphorylation Jiang and Ye, 2003) or direct modulation of the ion channel by G protein bg subunits (Yevenes et al, 2003(Yevenes et al, , 2006(Yevenes et al, , 2008. In addition, the relevance of Gbg signaling has been recently shown using intracellular blocking peptides designed to alter the interaction between the TM3-TM4 intracellular domain of GlyR and Gbg (Guzman et al, 2009;San Martin et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…It is believed that ethanol effects on sensorial transmission, motor control, respiratory rhythms, and cognitive processing are caused by changes in the activity of several ligand-gated ion channels (1) and particularly through the potentiation of the glycine receptor (GlyR) 2 (2). The GlyR has been extensively studied as a molecular target for ethanol, and electrophysiological experiments have demonstrated that ethanol potentiates GlyR activity (3), as determined by increased glycine-evoked currents (4,5), an increased decay time constant in spontaneous synaptic events (6), increased probability of channel opening in single-channel analysis (7), and increased agonist affinity (8). It was shown previously that G proteins participate in the ethanol effect on the GlyR (4).…”
mentioning
confidence: 99%